Teachers applying minimal pairs and its importance for using and recognition of the phonemes which represent ch, sh, k - Guillén Guillén, Winston Edmundo (Machala: Unidad Técnica de Machala, 2016)
This current essay states in a detailed way that English teachers must be aware of the existence of phonetics and an alphabet, introduces the International Phonetic Alphabet showing only the consonants, showing how the sounds is produced and what happens when it is ellocuted. It submits three voiceless phonemes. The way these phonemes are paired and introduces some activities on how to distinguish each one, and put them in a list where learners should recognize which is which. Moreover it gives some examples with pictures and phonetic transcription, letting the readers interact with the three sounds by placing them in the list they would belong. It remarks the importance of the International Phonetic Alphabet in providing a sound to each letter and their utterances. The grapheme "ch" sometimes sounds as if words where written with one either phoneme of /k/ and /ʃ/. Therefore it has devoted an interesting activity to deal with.
Keywords: VOICELESS PHONEMES; PAIR WORK